(untitled) (Research, Society and Development, 2021)
This study aimed to describe the epidemiological profile of food poisoning in Brazil with its trends and prospects for prevention, between the years 2016 and 2020. A cross-sectional, retrospective study with a quantitative approach was developed, the data for the research were taken from official government websites, namely: SINITOX (National System of Toxic-Pharmacological Information), DATASUS and IBGE (Brazilian Institute of Geography and Statistics). It became evident that a significant and sharp decrease in cases of food poisoning in Brazil and in its five socio-political regions (p<0.0001) in the year 2020, such fact being probably related to the advent of the COVID-19 pandemic. Regarding the occurrence of food poisoning by gender there was predominance in males with a sharp and significant decrease in the year 2020 for both genders. The age group between 15-19 years was the most prevalent, followed by children under 1 year old. Thus, it can be concluded that food poisoning is closely related to food consumption outside the home, reinforcing the importance of the professional nutritionist as a propagator of good hygiene, handling, and healthy eating practices.